Soil-borne disease suppressiveness after short and long term application of fermented, composted or fresh organic amendment treatments in arable soils - van der Sloot, Maartje; Maerowitz-Mcmahan, Solomon; Postma, Joeke; Limpens, Juul; De Deyn, Gerlinde B. (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2024)
Soil-borne diseases can cause significant crop losses and should be tackled sustainably in agroecosystems. Increasing the capacity of soils to suppress the effects of soil-borne diseases (soil suppressiveness) is an important tool in sustainable crop production. Soil suppressiveness can be improved by adding organic amendments to the soil for multiple years, but the effects can vary greatly depending on the processing method of the organic amendment (composted, fermented, or fresh material) and the time since application. To test these impacts we conducted two bioassays using the Lepidium savitum (cress) – Pythium ultimum model system. We tested the disease suppression capacity of sandy arable soil from a field experiment where fresh plant material, compost, or Bokashi (fermented amendment), all originating from the same plant material had been applied for two consecutive years across 10 field sites subject to conventional farming. In addition, the effect of short term application on soil suppressiveness was tested right after applying the same organic amendments to control arable sandy soil from 2 sites from the field experiment. Field sites strongly differed in cress growth independent of the organic amendment treatments. Absence of field effects in the sterilized soil and their soil chemical characteristics suggested differences in inherent soil pathogen load between the field sites. Focussing on sites with low inherent pathogen load we found no significant impact of long term organic amendment application on either cress weight or soil suppressiveness. However, short term application of Bokashi did significantly promote soil suppressiveness. This effect can likely be attributed to the increased metabolic activity of the soil's microorganisms in response to Bokashi, which contains more easily decomposable compounds as compared to the other soil amendments, together with Bokashi microorganisms that survive the fermentation and are activated in the aerobic soil condition. Our results suggest that Bokashi could promote the suppression of soil-borne diseases by stimulating the locally adapted soil microbiome but the longevity of this effect requires further field tests. •Fermented, composted and fresh organic amendments differ in soil suppressiveness.•Fermented organic material can improve soil suppressiveness in short term.•High soil pathogen load limits the impact of amendments on disease suppressiveness.